Multidisciplinary rehabilitation program: Effects of a multimodal intervention for patients with Alzheimer’s disease and cognitive impairment without dementia - Santos, Glenda Dias; Nunes, Paula Villela; Stella, Florindo [UNESP]; Brum, Paula Schimidt; Yassuda, Monica Sanches [UNESP]; Ueno, Linda Massako; Gattaz, Wagner Farid; Forlenza, Orestes Vicente (FapUNIFESP (SciELO), 2015)
Background: Non-pharmalogical interventions represent an important complement to standard pharmalogical treatment in dementia. Objective: This study aims to evaluate the effects of a multidisciplinary rehabilitation program on cognitive ability, quality of life and depression symptoms in patients with Alzheimer’s disease (AD) and cognitive impairment without dementia (CIND). Methods: Ninety-seven older adults were recruited to the present study. Of these, 70 patients had mild AD and were allocated into experimental (n = 54) or control (n = 16) groups. Two additional active comparison groups were constituted with patients with moderate AD (n = 13) or with CIND (n = 14) who also received the intervention. The multidisciplinary rehabilitation program lasted for 12 weeks and was composed by sessions of memory training, recreational activities, verbal expression and writing, physical therapy and physical training, delivered in two weekly 6-hour sessions. Results: As compared to controls, mild AD patients who received the intervention had improvements in cognition (p = 0.021) and quality of life (p = 0.003), along with a reduction in depressive symptoms (p < 0.001). As compared to baseline, CIND patients displayed at the end of the intervention improvements in cognition (p = 0.005) and depressive symptoms (p = 0.011). No such benefits were found among patients with moderate AD. Discussion: This multidisciplinary rehabilitation program was beneficial for patients with mild AD and CIND. However, patients with moderate dementia did not benefit from the intervention.
Keywords: Alzheimer disease; Impairment cognitive without dementia; Multidisciplinary rehabilitation program; Multimodal intervention